2020
DOI: 10.1016/j.psj.2020.01.020
|View full text |Cite
|
Sign up to set email alerts
|

Effects of temperature on quality of preserved eggs during storage

Abstract: The effects of storage temperature (4°C, 25°C, and 35°C) on sensory quality, physicochemical properties, texture, molecular forces, flavor, and microbial indexes of preserved eggs were studied. The results showed that the sensory quality, weight loss rate, pH, and color of preserved eggs were significantly different at different storage temperatures ( P < 0.05). Compared with high temperature and normal temperature storage, low temperature storage reduced weight loss rate by 55.15 and 64… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 38 publications
1
15
0
Order By: Relevance
“…While the relationship between the value of the Haugh unit and the yolk index was minimal when stored at 4 °C and 25 °C, the value of the weight loss rate was significantly related (R 2 = 0.988) in these two conditions, similar to previously published work. The weight loss rate of preserved eggs increased ( p < 0.05) as the storage time and temperature increased [ 21 ]. These results confirm that weight loss rate is a sensitive index that reflects egg freshness.…”
Section: Resultsmentioning
confidence: 99%
“…While the relationship between the value of the Haugh unit and the yolk index was minimal when stored at 4 °C and 25 °C, the value of the weight loss rate was significantly related (R 2 = 0.988) in these two conditions, similar to previously published work. The weight loss rate of preserved eggs increased ( p < 0.05) as the storage time and temperature increased [ 21 ]. These results confirm that weight loss rate is a sensitive index that reflects egg freshness.…”
Section: Resultsmentioning
confidence: 99%
“…Endogenous lipase was the main factor that caused the degradation of lipid. Thus, the triglycerides and phospholipids in PEY lipid were hydrolyzed to free fatty acids ( Luo et al, 2020 ). However, with the passage of pickling time, the alkalinity of PEY increased, which inhibited the activity of acid lipase in the yolk.…”
Section: Resultsmentioning
confidence: 99%
“…Fedde et al [59] found out that the quality parameters of eggs stored for 9 weeks in the cold were simiar to those observed for eggs stored at room temperature for 3 weeks. Refrigeration storage at (4 ± 2) • C is able to maintain safety and nutritive value of table eggs for approximately 4-5 weeks [60][61][62][63]. A decrease in HU from 91.4 to 76.3 was reported for eggs stored at 5 • C for 10 days [64].…”
Section: Discussionmentioning
confidence: 99%